GFRα1 Promotes Axon Regeneration after Peripheral Nerve Injury by Functioning as a Ligand - Tomoaki Suzuki; Ken Kadoya; Takeshi Endo; Miwako Yamasaki; Masahiko Watanabe; Norimasa Iwasaki (Advanced Science)
Abstract The neurotrophic factor, Glial cell line derived neurotrophi factor (GDNF), exerts a variety of biological effects through binding to its receptors, GDNF family receptor alpha‐1 (GFRα1), and RET. However, the existence of cells expressing GFRα1 but not RET raises the possibility that GFRα1 can function independently from RET. Here, it is shown that GFRα1 released from repair Schwann cells (RSCs) functions as a ligand in a GDNF‐RET‐independent manner to promote axon regeneration after peripheral nerve injury (PNI). Local administration of GFRα1 into injured nerve promoted axon regeneration, even more when combined with GDNF blockade. GFRα1 bound to a receptor complex consisting of NCAM and integrin α7β1 of dorsal root ganglion neurons in a GDNF‐RET independent manner. This is further confirmed by the Ret Y1062F knock‐in mice, which cannot transmit most of GDNF‐RET signaling. Finally, local administration of GFRα1 into injured sciatic nerve promoted functional recovery. These findings reveal a novel role of GFRα1 as a ligand, the molecular mechanism supporting axon regeneration by RSCs, and a novel therapy for peripheral nerve repair.